Pilot Study: Texture Analysis of PET Imaging Demonstrates Changes in 18F-FDG Uptake of the Brain After Prophylactic Cranial Irradiation. - Sawyer, David M.; Sawyer, Travis W.; Eshghi, Naghmehossadat; Hsu, Charles; Hamilton, Russell J.; Garland, Linda L.; Kuo, Phillip H. (Journal of Nuclear Medicine Technology, 2020)
Prophylactic cranial irradiation (PCI) is used to decrease the probability of developing brain metastases in patients with small cell lung cancer and has been linked to deleterious cognitive effects. Although no well-established imaging markers for these effects exist, previous studies have shown that structural and metabolic changes in the brain can be detected with MRI and PET. This study used an image processing technique called texture analysis to explore whether global changes in brain glucose metabolism could be characterized in PET images. Methods:18F-FDG PET images of the brain from patients with small cell lung cancer, obtained before and after the administration of PCI, were processed using texture analysis. Texture features were compared between the pre- and post-PCI images. Results: Multiple texture features demonstrated statistically significant differences before and after PCI when texture analysis was applied to the brain parenchyma as a whole. Regional differences were also seen but were not statistically significant. Conclusion: Global changes in brain glucose metabolism occur after PCI and are detectable using advanced image processing techniques. These changes may reflect radiation-induced damage and thus may provide a novel method for studying radiation-induced cognitive impairment.